2008
DOI: 10.1111/j.1439-0396.2007.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of induced subacute ruminal acidosis on milk fat content and milk fatty acid profile

Abstract: Two lactating dairy cows fitted with a rumen cannula received successively diets containing 0%, 20%, 34% and again 0% of wheat on a dry matter basis. After 5, 10 and 11 days, ruminal pH was measured between 8:00 and 16:00 hours, and milk was analysed for fat content and fatty acid profile. Diets with 20% and 34% wheat induced a marginal and a severe subacute ruminal acidosis respectively. After 11 days, diets with wheat strongly reduced the milk yield and milk fat content, increased the proportions of C8:0 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 28 publications
7
49
1
2
Order By: Relevance
“…The fat % of the total milk in the bulk tank was within normal range (tab.4). These results agree with those reported by Kleen et al (2003);; Enjalbert et al (2008) and Bipin et al (2016) but not agree with Oetzel, (2005);Tajik et al (2009) who reported that SARA had no effect on milk fat % in farm condition.…”
Section: Discussionsupporting
confidence: 80%
“…The fat % of the total milk in the bulk tank was within normal range (tab.4). These results agree with those reported by Kleen et al (2003);; Enjalbert et al (2008) and Bipin et al (2016) but not agree with Oetzel, (2005);Tajik et al (2009) who reported that SARA had no effect on milk fat % in farm condition.…”
Section: Discussionsupporting
confidence: 80%
“…Milk odd-and branched-chain FA (OBCFA) are of particular interest in this respect because they have been linked to the rumen fermentation pattern (Vlaeminck et al, 2006b;Cabrita et al, 2007;Craninx et al, 2008). Moreover, accumulation of FA during rumen biohydrogenation depends on the rumen environment, with predominant switches toward the C18:1 trans-10 pathway at low ruminal pH (e.g., Enjalbert et al, 2008). Because of these relationships and the ease of obtaining milk samples, monitoring the FA profile of milk has potential value in the diagnosis of SARA and could facilitate its prevention.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proportion used could have affected the ruminal pH, which then affected the IMF fatty acid profile. Enjalbert et al (2008) reported lower contents of C18:0 and CLA c-9 t-11 in milk fat when wheat grain was added to the diet to induce SARA. Colman et al (2010) also found that the concentrations of C18:0 and CLA c-9 t-11 in milk fat were lower in the third week postinduction of mild SARA with wheat grain in the diet.…”
Section: Intramuscular Fatty Acid Compositionmentioning
confidence: 99%
“…However, the pH of the rumen is primarily influenced by the fermentable carbohydrate in the diet, and the amount and source of starch and/or the rate of ruminal degradation of starch affects biohydrogenation in the rumen (Mohammed et al, 2010). Wheat grain reduces the ruminal pH and is used to induce subacute ruminal acidosis (SARA); subacute ruminal acidosis results in changes of the fermentation pattern in the rumen, with possible changes in the production of fatty acids (Enjalbert et al, 2008). These authors reported that diets with 20 and 34% wheat induced a marginal or a severe SARA, respectively.…”
Section: Intramuscular Fatty Acid Compositionmentioning
confidence: 99%